Repositioning Libraries as National Knowledge Infrastructure for Viksit Bharat 2047 - Hasan, Nabi (Journal of Data Science, Informetrics, and Citation Studies, 2026)
India’s Vision Viksit Bharat 2047 sets a clear national mandate to transform the country into a developed, knowledge-driven, and innovation-led economy by the centenary of its independence. Achieving this vision requires positioning libraries as core national infrastructure rather than peripheral support systems. This article argues that libraries must be strategically integrated into governance, research, and innovation frameworks as enablers of digital inclusion, evidence-based policymaking, and knowledge equity. It critically examines their transition from traditional repositories to intelligent, data-driven, and user-centric knowledge hubs, drawing on institutional practices such as the IIT Delhi Library system. The analysis highlights the urgent need to scale digital transformation, research support services, open access, and the adoption of emerging technologies, including artificial intelligence and data analytics. It calls for policy-driven investment, capacity building, and institutional alignment to strengthen library ecosystems as a prerequisite for a globally competitive, sustainable knowledge economy under Viksit Bharat 2047.
Keywords: Developed India 2047; Digital Transformation in Libraries; Evidence-Based; Governance; Knowledge economy; Research and Innovation Ecosystems; Viksit Bharat 2047